Reversible desensitization of the myocardial contractile apparatus forcalcium: a new concept for improving tolerance to cold ischemia in humanmyocardium? - Vahl, Christian-Friedrich; Bonz, Andreas Wolfgang; Hagl, Christian Matthias; Hagl, Siegfried (European journal of cardio-thoracic surgery, 1994)
The influence of 2,3-Butanedione monoxime (BDM) on the humanmyocardium's tolerance to cold ischemia was analyzed in two experimentalseries. Methods: I) Left ventricular human muscle fibers (0.6 x 4.0 mm)were obtained from recipient hearts (n = 10) and loaded with thefluorescent dye Fura-2. Simultaneous measurements of intracellular calciumtransients ("ratio-method"; excitation wave lengths: 340 nm and 380 nm) andisometric force development of electrically driven (1 Hz) muscle fiberswere carried out at BDM concentrations ranging from 0 to 30 mM at a bathtemperature of 37 degrees C; II) Left ventricular human muscle strips wereobtained from beating recipient hearts (n = 10), and right atrial fibersfrom patients operated upon for aortic valve stenosis or combined mitralvalve disease (n = 14). Muscle strips of these hearts were incubated forparallel measurements in the following solutions: a) a 37 degrees Coxygenated Krebs-Henseleit solution (KHS), b) a 4 degrees C Bretschneider'scardioplegic solution (HTK) without oxygenation and c) a 4 degrees C KHScontaining 30 mM BDM without oxygenation (BDM solution). After standardizedtime intervals the muscle fibers were removed from the storage solutions,reperfused in KHS solution at 37 degrees C and stretched to optimal length(supramaximal electrical stimulation). After obtaining a steady state offorce development, the contractile behavior under isometric and isotonicmeasurement conditions was measured. The influence of the incubationperiods and the incubation solution was analyzed. Results: I) BDM reducedthe isometric force development of the electrically driven isolated humanmyocardial muscle strip in a dose-dependent way.(ABSTRACT TRUNCATED AT 250WORDS)
Gesehen am 16.06.2025